ChemInform Abstract: Highly Efficient Direct Aerobic Oxidative Esterification of Cinnamyl Alcohol with Alkyl Alcohols Catalyzed by Gold Nanoparticles Incarcerated in a Nanoporous Polymer Matrix: A Tool for Investigating the Role of the Polymer Host. Issue 40 (30th September 2014) - Buonerba, Antonio; Noschese, Annarita; Grassi, Alfonso
Abstract Direct aerobic oxidation and oxidative esterification of cinnamyl alcohol is achieved using gold nanoparticles supported in a semicrystalline multi‐block polystyrene‐co‐cis‐1, 4‐polybutadiene matrix as the catalyst (all yields determined by GC‐analysis using anisole as an internal standard).